Sustainable Vaname Shrimp Agribusiness Development Model in Parigi Moutong Regency, Central Sulawesi Province - Muhammad Nasir; Made Antara; Arifuddin Lamusa (Postgraduate, University of Mataram, 2025)
This study aims to identify and evaluate a sustainable model, as well as assess the sustainability of whiteleg shrimp farming in Parigi Moutong Regency. The assessment of sustainability will be conducted using the Rapfish approach, which includes five dimensions that are customized to the specific research area to provide an accurate representation of the present state. The results of the study indicate that whiteleg shrimp farming in Parigi Moutong Regency has a satisfactory and stable level of sustainability, indicated by an overall index value of > 50% through the Rapfish approach. In order to address the challenges in managing white shrimp resources, such as coastal habitat destruction, overfishing, and lack of coordination among institutions, the government of Parigi Moutong Regency needs to establish integrated and coordinated cooperation with stakeholders.